2006
DOI: 10.1007/s10750-006-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal consistency in the long-term spatial distribution of macroinvertebrate drift along a stream reach

Abstract: Previous studies of the spatial pattern of stream invertebrate drift have focused on spatial variation at microhabitat scales or landscape scales, or temporal variation over diel or seasonal scales. None have examined consistency in spatial variation over longer time scales (>1 year). This study examined invertebrate drift density and composition at fixed locations (terminal ends of 10 riffles) each month at day and night along a 1 km reach of a 2nd order stream over a period of nearly 2 years. Consistent diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 55 publications
9
31
1
Order By: Relevance
“…The daily variation in the drift is a recurring pattern, with numerous studies showing that drift increases at night, especially just after sunset (Poff and Ward, 1991;Ramı´rez and Pringle, 1998;Hansen and Closs, 2007). Nevertheless, we did not observe a recurring pattern of daily drift in both wet and dry seasons.…”
Section: Discussioncontrasting
confidence: 56%
“…The daily variation in the drift is a recurring pattern, with numerous studies showing that drift increases at night, especially just after sunset (Poff and Ward, 1991;Ramı´rez and Pringle, 1998;Hansen and Closs, 2007). Nevertheless, we did not observe a recurring pattern of daily drift in both wet and dry seasons.…”
Section: Discussioncontrasting
confidence: 56%
“…Numerous studies have shown that drift increases at night, especially just after sunset (Poff and Ward, 1991;Ramírez and Pringle, 1998;Hansen and Closs, 2007). However in the wet season with fixed flows, we observed no differences in drift between differing sampling periods (Figure 7).…”
Section: Discussionmentioning
confidence: 41%
“…The downstream transport of invertebrates is not constant and varies with season, day, and time of day (Brittain and Eikeland, 1988). Differences in drift densities may also vary by species and life cycle stage (Hansen and Closs, 2007). Macroinvertebrate drift is very important to aquatic ecosystem function, because it is a primary mechanism for the redistribution and colonisation of aquatic macroinvertebrates (Hay et al, 2008) and offers prey for predators such as fish (Flecker, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The flow regulation and stratification patterns developed in reservoirs frequently impact the biota downstream in four ways (Cortes et al 2002): i) alteration of physical and chemical characteristics associated with the release of water and sediment derived from the hypolimnion, that affect life history and density of macroinvertebrates (Cortes et al 2002); ii) alteration of available food resources to aquatic biota, specially through changes in the particulate organic matter (McAllister et al 2001); iii) creation of unstable environment due to daily changes in water level, increasing invertebrate drift (Hansen and Closs 2007); and iv) reduction of water released downstream, which modify abundance and diversity of benthic fauna (Bunn and Arthington, 2002). These effects have been demonstrated in several regulated rivers, where alterations in discharge have caused changes in the structure of the aquatic community (Pardo et al, 1998;Rosin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%